2016
DOI: 10.1007/s10549-016-4034-2
|View full text |Cite
|
Sign up to set email alerts
|

Frequency of pathogenic germline mutation in CHEK2, PALB2, MRE11, and RAD50 in patients at high risk for hereditary breast cancer

Abstract: Pathogenic variants in CHEK2, PALB2, MRE11, and RAD50 were detected in a small proportion of Korean patients with features of hereditary breast cancer.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
27
3

Year Published

2017
2017
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 29 publications
(36 citation statements)
references
References 39 publications
6
27
3
Order By: Relevance
“…A total of 11 VUSs discovered here in ATM were reported previously. We found 1 deleterious germline mutation in CHEK2 (c.1245dupC), which was recently reported in Korean breast cancer patients . All 10 VUSs in CHEK2 were reported previously in ClinVar or Exome Aggregation Consortium.…”
Section: Discussioncontrasting
confidence: 85%
See 3 more Smart Citations
“…A total of 11 VUSs discovered here in ATM were reported previously. We found 1 deleterious germline mutation in CHEK2 (c.1245dupC), which was recently reported in Korean breast cancer patients . All 10 VUSs in CHEK2 were reported previously in ClinVar or Exome Aggregation Consortium.…”
Section: Discussioncontrasting
confidence: 85%
“…13 Deleterious PALB2 mutations were found in familial breast cancer with a prevalence of about 1% to 4% and .1% to 1% in unselected breast cancer. 30,40,41 In our study, only 1 novel deleterious mutation (.34%) was detected in PALB2. Although all PALB2 VUSs were predicted to be tolerant, there were 3 germline VUSs (PALB2 c.2673C>G, c.3054G>C and c.3139A>G) and 1 somatic VUS (PALB2 c.3139A>G) located in the WD40-repeat-containing domain of PALB2 that could affect PALB2 binding to the N-terminus of BRCA2.…”
Section: The Clinicopathological Characteristics Of Mutation Carrierscontrasting
confidence: 49%
See 2 more Smart Citations
“…evaluated the frequency of pathogenic RAD50 germline mutations among Korean patients at high risk for hereditary breast cancer. They reported a pathogenic RAD50 mutation rate of 0.85% in participating patients . In the current study, we found that 0.34% of our study population had a pathogenic RAD50 mutation, indicating that such mutations are infrequent.…”
Section: Discussionsupporting
confidence: 53%